“BYKHOV PERIOD” OF RUSSIAN GENERAL KORNILOV - N. V. Shevtsov (Vestnik MGIMO-Universiteta)
The end of August 1917 was marked by a dramatic event, which influenced a lot the future of the Russian state. It is the case of the so-called «Kornilov revolt» – undertaken by the Supreme Commander-in-Chief General L.G. Kornilov, who attempted to send troops to Petrograd in order to establish military order in the capital. Kornilov’s action was unsuccessful. Together with his closest associate she was arrested and sent to a small Belarusian town of Old Bykhov, located near Mogilev, where the headquarters was located. The generals L.G. Kornilov, A.I. Denikin, A.S. Lukomsky, S.L. Markov and other prominent figures of the White movement were soon placed in a converted women’s gymnasium in a prison. There they were about a month and a half, and then, shortly after the October events of 1918, they left it going to the Don. “The Kornilov revolt” has been devoted to a lot of books and scientific articles, but very few have been written about the stay of military commanders were held in the prison of the Belarusian town. More details about him were written, perhaps, only by A.I. Denikin in the work «Essays of the Russian Troubles». The absence of numerous sources about the «Bykhov period» of Kornilov and his associates can be explained by three reasons. First, Kornilov and his associates were in isolation in Bykhov and could not communicate with their recent political military environment. Journalists also did not have access to them, so articles in the newspapers about what happened to the Bykhovites appeared quite infrequently. Secondly, Kornilov’s stay in Bykhov turned out to be extremely short. Finally, those who could leave interesting memories, for example, the same Kornilov or Markov, died in less than a year on the fronts of the Civil War. Having decided partly to fill the gap in the historiography of the “Bykhov period”, the author visited the town of Bykhov, which is now located in the Mogilev region in Belarus, and tried to find evidence of the presence of participants in Kornilov’s actions in August 1918. He visited the building of the former women’s gymnasium, which now houses the Bykhov forestry. Then he saw the room in which Kornilov lived. Its layout has not changed much. In the same building, the forestry staff created a small museum exposition. Near the main entrance there is a memorial plaque informing about the stay of Kornilov in Bykhov. During the preparation of the article, author also held some conversations with the director of the historical museum of this city, as well as with L.A. Kornilov - Chapron du Lorre – grandson of the famous general, who lives now in Brussel. He told a lot of interesting things about the events which happened in late August 1917.